2008
DOI: 10.1002/marc.200700851
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Route to Synthesize Well‐Defined Polybutadiene DendriMacs

Abstract: A facile route to synthesize well‐defined polybutadiene (PBd) DendriMacs is described. In a highly modified approach to that recently published for the synthesis of polystyrene DendriMacs, a G1 polybutadiene (PBd) DendriMac has been synthesized in three simple and high yielding steps. The first step involves the synthesis of a three‐arm PBd mikto arm star in which one arm has a terminal hydroxy group introduced by the use of a protected functionalized initiator. Following fractionation of the star, the hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 12 publications
(19 reference statements)
0
61
0
Order By: Relevance
“…A mole ratio of 2.5 : 1 (long arm : short arm) was used in all cases. This mole ratio has been shown to be optimal for analogous reactions described elsewhere [33,38]. As well as describing the two synthetic strategies we will compare the efficiency of the two approaches.…”
Section: Synthesis Of Starsmentioning
confidence: 99%
See 3 more Smart Citations
“…A mole ratio of 2.5 : 1 (long arm : short arm) was used in all cases. This mole ratio has been shown to be optimal for analogous reactions described elsewhere [33,38]. As well as describing the two synthetic strategies we will compare the efficiency of the two approaches.…”
Section: Synthesis Of Starsmentioning
confidence: 99%
“…Star polymers with varying numbers of arms have been widely produced and studied [1][2][3][4][5][6][7][8] and branched polymers of increasing complexity and diverse structures have evolved. These include H-shaped polymers [9][10][11][12][13][14][15], comb-shaped polymers [16][17][18][19][20][21][22][23][24][25][26][27][28] and more recently dendritically branched polymers [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Fundamental to all these studies is the ability of the synthetic polymer chemist to control structural homogeneity and produce branched ...…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quirk et al 36 have previously reported arm cleavage when hydrolysis was carried out for a prolonged reaction time in an identical deprotection reaction on similar star branched polymers: an observation that we also initially made during the synthesis of the DendriMac. 17 To minimize arm cleavage, the deprotection reaction was carried out under high vacuum for only 30 min in presence of BHT (0.1% w/w) at 70°C, however, it is possible that arm cleavage was not completely eliminated. Although the intermediate star was fractionated to give a monomodal, narrow polydispersity peak, it is likely that SEC would be unable to resolve the star from traces of the defect with one of the shorter arms missing, and such a defect would be able to take part in the subsequent coupling reactions to form the DendriMac.…”
Section: Acs Macro Lettersmentioning
confidence: 99%